2010
DOI: 10.1007/s11664-010-1141-4
|View full text |Cite
|
Sign up to set email alerts
|

HgCdTe Growth on 6 cm × 6 cm CdZnTe Substrates for Large-Format Dual-Band Infrared Focal-Plane Arrays

Abstract: This paper describes molecular-beam epitaxy growth of mid-wavelength infrared (MWIR) and long-wavelength infrared (LWIR) dual-band device structures on large-area (6 cm 9 6 cm) CdZnTe substrates. Wafer-level composition and defect mapping techniques were used to investigate the limiting mechanisms in improving the cutoff wavelength (k c ) uniformity and reducing the defect density. Structural quality of epitaxial layers was monitored using etch pit density (EPD) measurements at various depths in the epitaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In 1985, Rogalski A. and Larkowski W. proposed p-on-n configuration [38], shown in Figure 3c, and demonstrated its advantage of operating at high temperature. A series of configurations based on p-on-n configuration have been proposed and manufactured, such as double-layer heterojunction (DLHJ) [54] and double-layer planar heterostructure (DLPH) [55]. In the 1990s, the third generation of photodetectors focused on very large FPAs.…”
Section: Hg X Cd 1−x Te Mwir and Lwir Photodetectormentioning
confidence: 99%
“…In 1985, Rogalski A. and Larkowski W. proposed p-on-n configuration [38], shown in Figure 3c, and demonstrated its advantage of operating at high temperature. A series of configurations based on p-on-n configuration have been proposed and manufactured, such as double-layer heterojunction (DLHJ) [54] and double-layer planar heterostructure (DLPH) [55]. In the 1990s, the third generation of photodetectors focused on very large FPAs.…”
Section: Hg X Cd 1−x Te Mwir and Lwir Photodetectormentioning
confidence: 99%
“…[9] It is observed that HgCdSe alloy is nearly lattice matched to GaSb substrate, which is a high-quality III-V substrate with features of larger wafer size (up to 6 inches in diameter), lower wafer cost, and higher crystal quality (etch pit density as low as < 10 3 cm −2 ). [3,6] Considering that the lattice mismatch between HgCdSe layer and GaSb substrate is only around 0.4%, the ultimate dislocation density in HgCdSe layers grown on GaSb should be below the level of 10 5 cm −2 , which will be comparable to that in HgCdTe grown on latticematched CdZnTe substrates, [10] and thus be suitable for making high-performance infrared detectors. In the meantime, as shown in Fig.…”
Section: Hgcdse Infrared Materials and Detectorsmentioning
confidence: 99%
“…17 and 18 that both FPAs show some of the highest pixel operabilities and low cluster outages. 8,10 Improved composition uniformity on these wafers helped achieve higher operability by minimizing the variability in pixel k c and the associated dark current variations 11 across the FPAs. Further, the low cluster outages in these FPAs can be attributed to the low density of relatively larger defects (size >30 lm) on these wafers.…”
Section: Hgcdte On Cdzntementioning
confidence: 99%